Cytologic–histologic concordance in the diagnosis of neoplasia in canine and feline lymph nodes: a retrospective study of 367 cases. (15th August 2016) - Ku, C.‐K.; Kass, P. H.; Christopher, M. M.
Abstract: Lymph nodes are frequently sampled in dogs and cats for the diagnosis of primary and metastatic neoplasia. We determined the accuracy of cytologic diagnosis in lymph nodes using histology as the gold standard. Lymph node reports (2001–2011) were retrospectively evaluated and diagnoses were categorized as neoplastic or non‐neoplastic. Lymph nodes from 296 dogs and 71 cats included 157 (42.7%) non‐neoplastic lesions, 62 (16.9%) lymphomas and 148 (40.3%) metastatic neoplasms. Cytology had a sensitivity of 66.6% [95% confidence interval (CI) 60.0–72.8%], specificity of 91.5% (CI 86.3–95.2%), and accuracy of 77.2% (CI 72.6–81.3%) for neoplasia. Likelihood of malignancy with a positive cytologic diagnosis of neoplasia was 93.0%. High proportions of false‐negative results were found in mesenteric T‐cell lymphoma (22/35, 63%, mainly cats), metastatic sarcoma (8/14, 57%) and metastatic mast cell tumour (15/48, 31%, mainly dogs). Factors contributing to discrepancies included well‐differentiated lymphocyte morphology, focal distribution of metastases and poorly defined criteria for metastatic mast cell tumours.